Preparation method of electromagnetic wave absorbing composite film and application of obtained product

CN116496527BActive Publication Date: 2026-10-27NANTONG QIANJIUXING TECHNOLOGY NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310683277.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2026-10-27
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

但传统的吸波材料主要作为涂层涂覆在目标物体表面,在潮湿的环境中易脱落,使用范围受到限制

Benefits of technology

[0024](1)本发明结合水热反应和热解法法制得Ni/CMT/PTFE复合材料,制备工艺简便易行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496527B_ABST
    Figure CN116496527B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an electromagnetic wave absorption composite film and application of the obtained product, and steps are as follows: carbonizing kapok fibers to obtain carbon microtubules; growing nickel-metal organic frameworks on the surface and inside of the carbon microtubules through a hydrothermal method to obtain nickel-metal organic framework / carbon microtubules; high-temperature carbonizing the nickel-metal organic framework / carbon microtubules to obtain nickel / carbon microtubules; and finally dispersing the nickel / carbon microtubules in a polytetrafluoroethylene solution to obtain a nickel / carbon microtubule / polytetrafluoroethylene composite material. The nickel / carbon microtubule / polytetrafluoroethylene composite film is prepared by taking polytetrafluoroethylene as a skeleton, high-temperature pyrolysis and a hydrothermal method, the process is simple, and the shortcomings of poor dispersibility of carbon materials, easy falling-off of traditional wave-absorbing coatings, lack of flexibility and difficulty in use in extreme environments are effectively solved, the nickel / carbon microtubule / polytetrafluoroethylene composite film has good flexibility, conductivity, thermal conductivity and excellent electromagnetic wave absorption performance, and has wide application value in fields of weapon equipment stealth, electromagnetic wave pollution protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing an electromagnetic wave absorbing composite thin film, and also to the product obtained by the method and its application in the fields of electromagnetic wave absorption and thermally conductive fillers, belonging to the field of nanomaterial preparation and application technology. Background technology:

[0002] With the rapid development of communication technology and the increasing number of small mobile electronic devices, serious electromagnetic pollution problems have inevitably arisen, including interference with communication systems, impacts on human health, and potential explosions. The commercialization of emerging, highly miniaturized and integrated 5G wireless devices requires microwave absorbing materials (MAMs) to be easy to process, have thin coatings, be lightweight, and possess mechanical elasticity, capable of transferring heat and electrical energy while exhibiting enhanced microwave absorption capabilities. However, current research focuses on optimizing impedance matching and improving electromagnetic response by adjusting their morphology and composition, with little attention paid to enhancing their environmental adaptability under extreme conditions such as low temperatures, high humidity, and snow. For example, the additional gravitational load imposed by ice accumulation can cause mechanical damage to wings, thereby compromising aircraft handling stability. Furthermore, coating detachment due to freezing can disable the microwave absorption (MA) performance of weapons such as stealth aircraft and warships. Although MAMs are experiencing rapid growth, research linking them to de-icing is very limited. Therefore, there is an urgent need to develop an MA absorber with excellent waterproof and de-icing properties, better suited to the future needs of the intelligent era.

[0003] Traditional de-icing methods such as rubber scraper de-icing, hot air de-icing, and chemical de-icing inevitably have various limitations and cannot fully meet the high requirements of modern stealth weapons. For example, aircraft de-icing sprays typically contain ethylene glycol, a compound known for lowering the freezing point of water. However, its application is limited due to its environmental unfriendliness, short anti-icing time, and susceptibility to aircraft surface corrosion. To overcome these shortcomings, further designing and innovating efficient de-icing strategies utilizing sustainable energy is crucial. Recent research has shown that the photothermal effect provides a new pathway for de-icing, melting ice by converting light energy into heat energy. However, its de-icing capacity is limited when the system operates at night without sunlight. Introducing the electrothermal effect is one of the most attractive strategies for maintaining continuous de-icing capability. Utilizing the heat generated by the Joule heating effect can achieve heat preservation de-icing, which is beneficial for keeping aircraft surfaces clean under adverse weather conditions, improving flight safety and performance. Adding carbon materials to polymer networks is beneficial for improving the stability and durability of microwave absorbers. Although significant progress has been made, it inevitably has many fatal weaknesses. (1) The high conductivity of carbon materials leads to excessive conductivity loss, which easily causes a large amount of incident electromagnetic waves to be reflected rather than absorbed; (2) Pure carbon materials have a simple loss mechanism and poor impedance matching; (3) The interface thermal resistance between the matrix and pure carbon materials is large and the dispersion is poor, which limits their thermal management function. Therefore, the ingenious design of layered heterogeneous interfaces within the overall hollow carbon framework is a promising solution. In addition to the induced interfacial polarization between heterogeneous interfaces, the layered structure with abundant exposed surfaces can also act as a trap, effectively capturing electromagnetic waves through multiple internal reflections and scatterings. Furthermore, the layered hollow structure combines the advantages of a huge internal cavity and a large heterogeneous surface, significantly triggering strong interfacial polarization and optimizing impedance matching.

[0004] Therefore, there is an urgent need to explore flexible electromagnetic wave absorbing materials that are reasonably priced, stable, have thin coatings, and can operate in complex environments. However, traditional absorbing materials are mainly applied as coatings to the surface of target objects, which are prone to peeling off in humid environments, limiting their application. Therefore, developing a composite material with high electromagnetic wave absorption performance, good electrothermal properties, and thermal reliability through reasonable structural design and composition optimization is of great significance. Summary of the Invention

[0005] To address the shortcomings of CMT in electromagnetic wave absorption and mechanical flexibility, this invention provides a method for preparing an electromagnetic wave absorbing composite film and the application of the resulting product. The method is simple, optimizing the structure of CMT by modifying the surface of CMT with Ni nanoparticles, and finally encapsulating it with PFFE. The resulting composite material has a stable structure and good electrical conductivity, electromagnetic wave absorption performance, and thermal conductivity, and has wide application value in the fields of thermally conductive fillers and electromagnetic wave absorption.

[0006] The specific technical solution of this invention is as follows:

[0007] A method for preparing an electromagnetic wave absorbing composite thin film includes the following steps:

[0008] (1) CMT is obtained by calcining kapok fibers in a nitrogen atmosphere.

[0009] (2) Ni-MOF is grown on the surface and inside of CMT by hydrothermal reaction to obtain Ni-MOF / CMT.

[0010] (3) Ni-MOF / CMT is calcined in a nitrogen atmosphere to obtain Ni / CMT.

[0011] (4) Ni / CMT is dispersed in PTFE to obtain a flexible Ni / CMT / PTFE composite material.

[0012] Furthermore, the commercially available kapok fibers used in this invention generally have a diameter of 20-50 μm.

[0013] Furthermore, in step (1), the calcination temperature is 750-850℃, and the calcination time is 1-2h. The nitrogen gas flow rate is 30-40mL / min.

[0014] Furthermore, in step (2), the hydrothermal growth method for Ni-MOF can be carried out with reference to methods disclosed in the prior art. Preferably, the reactants are CMT, NiCl2·6H2O and H3BTC, and the solvent is dimethylformamide. The reaction time is 10-14 h.

[0015] Furthermore, in step (2), the concentration of NiCl2·6H2O is controlled between 0.014 g / mL and 0.015 g / mL, and the concentration of H3BTC is controlled between 0.0016 g / mL and 0.0017 g / mL. The concentration of CMT added is 0.8 mg / mL to 3 mg / mL. By adjusting the amount of CMT added, the morphology of Ni-MOF grown on the CMT framework is controlled. Experiments show that the amount of CMT added has a great influence on the morphology and performance of the final product, and is the key to the formation of the final product composition and morphology, as well as the key to the electromagnetic wave absorption performance of the composite material. Preferably, the amount of CMT added is 2.5 mg / mL.

[0016] Furthermore, in step (2), the mixture is reacted in a closed reactor for 10-14 hours.

[0017] Furthermore, in step (3), the calcination temperature is 350-500℃, and the calcination time is 1-2h. The nitrogen gas flow rate is 30-40mL / min.

[0018] Further, in step (4), Ni / CMT and PTFE are mixed uniformly at a certain mass ratio. The mass ratio is 1%-7%, for example, 1%, 3%, 5%, 7%. Then, a certain amount of ethanol is added and stirred uniformly. The volume ratio of ethanol to PTFE is 1-2:1. By adjusting the mass ratio of Ni / CMT and PTFE, the conductive network in the composite material can be controlled. Experiments show that CMT and PTFE have a significant impact on the final morphology and also have a certain impact on the electromagnetic wave absorption performance of the composite material. Preferably, the mass ratio of Ni / CMT and PTFE is 3%.

[0019] This invention obtains carbon microtubes (CMTs) by carbonizing kapok fibers; subsequently, a nickel-metal-organic framework (Ni-MOF) is grown on the surface and inside the CMTs via a hydrothermal method to obtain Ni-MOF / CMTs; next, the Ni-MOF / CMTs are carbonized at high temperature to obtain Ni / CMTs. Finally, the Ni / CMTs are dispersed in a polytetrafluoroethylene (PTFE) solution to obtain a Ni / CMT / PTFE composite material. The composite material obtained by this invention is a PTFE-encapsulated Ni / CMT composite film. This invention uses PTFE as a skeleton and prepares the Ni / CMT / PTFE composite film through high-temperature pyrolysis and hydrothermal processes. The process is simple and effectively solves the shortcomings of poor dispersion of carbon materials, easy peeling off of traditional microwave absorbing coatings, lack of flexibility, and difficulty in use in extreme environments. The composite material of this invention has good flexibility, electrical conductivity, and thermal conductivity. By adjusting the filling ratio of Ni / CMTs in the composite material, the electromagnetic wave absorption performance of the composite material can be precisely adjusted.

[0020] This invention also provides an electrothermal microwave absorber applicable in extreme environments, the raw material of which includes the aforementioned Ni / CMT / PTFE composite material. By adjusting the filling ratio of Ni / CMT in the composite material, the thermal conductivity and electrical conductivity of the microwave absorber can be adjusted, thereby adjusting the electrothermal performance of the microwave absorber, which has excellent application prospects.

[0021] The Ni / CMT / PTFE composite material obtained by this invention possesses excellent flexibility, electrical conductivity, thermal conductivity, and electromagnetic wave absorption performance. Furthermore, it exhibits structural stability and strong thermal stability, making it a promising candidate for applications in electromagnetic wave absorption and thermally conductive filler fields. This overcomes the shortcomings of purely traditional electromagnetic wave absorbing materials in these applications. Therefore, the Ni / CMT / PTFE composite material prepared by this invention and its application in electromagnetic wave absorption and thermally conductive filler fields are also within the scope of protection of this invention.

[0022] This invention uses CMT as a framework to prepare Ni / CMT / PTFE composite materials through hydrothermal reaction and pyrolysis. The process is simple and effectively solves the shortcomings of carbon materials, such as poor dispersion, easy peeling of traditional microwave absorbing coatings, lack of flexibility, and difficulty in use in extreme environments. It also significantly improves the electromagnetic wave absorption performance of CMT.

[0023] Compared with the prior art, the advantages of the present invention are as follows:

[0024] (1) The present invention combines hydrothermal reaction and pyrolysis to prepare Ni / CMT / PTFE composite material, and the preparation process is simple and easy to implement.

[0025] (2) The present invention prepares a flexible film of Ni / CMT / PTFE, which effectively solves the problem of easy peeling of traditional microwave absorbing coatings; by combining the characteristics of organic polymer PTFE and effective absorber Ni / CMT, the absorber-polymer composite film has excellent mechanical properties, chemical resistance, flexibility and excellent dielectric properties.

[0026] (3) The Ni / CMT / PTFE composite material prepared by this invention has good electrical conductivity and stable structure. Experiments have shown that its performance is significantly improved compared with pure CMT. Due to its stable structure, carbon material acts as a thermal bridge and has broad application prospects in thermal filling.

[0027] (4) The Ni / CMT / PTFE composite material prepared by this invention exhibits strong thermal stability, excellent electrical conductivity, and superior electromagnetic wave absorption performance, showing broad application prospects in electromagnetic wave absorption. These findings provide valuable insights for the design of advanced microwave absorbers to meet the requirements of electromagnetic encapsulation, waterproofing, de-icing, and fire resistance. Attached Figure Description

[0028] Figure 1 The images are scanning electron microscope (SEM) images of the prepared samples: where a and b are SEM images of kapok fibers, and c and d are SEM images of CMT fibers.

[0029] Figure 2 The images are Ni-MOF / CMT scanning electron microscope images: where ac is a Ni-MOF / CMT-50 scanning electron microscope image, df is a Ni-MOF / CMT-100 scanning electron microscope image, and gi is a Ni-MOF / CMT-150 scanning electron microscope image.

[0030] Figure 3 This is a scanning electron microscope image of Ni-MOF.

[0031] Figure 4 Images are electron microscope (EM) images of Ni / CMT; where a is a scanning electron microscope (SEM) image of Ni / CMT and b is a transmission electron microscope (TEM) image of Ni / CMT.

[0032] Figure 5 This is a scanning electron microscope image of PTFE.

[0033] Figure 6 The images are scanning electron microscope (SEM) images of Ni / CMT / PTFE: where a is an NCP-1 SEM image, b is an NCP-3 SEM image, c is an NCP-5 SEM image, and d is an NCP-7 SEM image.

[0034] Figure 7 Here are the electromagnetic parameters of Ni-MOF / CMT: where a and c are the real part of the dielectric (ε′), b and d are the imaginary part of the dielectric (ε″), e is the real part of the permeability (μ′), and f is the imaginary part of the permeability (μ″).

[0035] Figure 8 The value is the reflection loss (RL) of Ni-MOF / CMT.

[0036] Figure 9 Here are the electromagnetic parameters of Ni / CMT / PTFE: where a is the real part of the dielectric (ε′), b is the imaginary part of the dielectric (ε″), c is the real part of the permeability (μ′), and d is the imaginary part of the permeability (μ″).

[0037] Figure 10 The reflection loss (RL) value is for Ni / CMT / PTFE.

[0038] Figure 11 The images are digital photographs and thermal infrared images of Ni / CMT / PTFE; where a is a photograph and thermal infrared image of Ni / CMT / PTFE at different voltages; and b is a digital photograph and thermal infrared image of Ni / CMT / PTFE at a working voltage of 30V during the de-icing process. Detailed Implementation

[0039] The present invention will be described in detail below through specific embodiments. However, the uses and purposes of these exemplary embodiments are only for explaining and illustrating the present invention, and are not intended to limit the actual protection scope of the present invention in any way, nor to limit the protection scope of the present invention to these embodiments.

[0040] Example 1 Ni-MOF / CMT

[0041] (1) Synthetic CMT

[0042] Normally, kapok fibers are placed in a tube furnace and heat-treated at 800°C in a nitrogen atmosphere for 2 hours at a heating rate of 5°C / min. The resulting product is CMT.

[0043] (2) Synthesis of Ni-MOF / CMT

[0044] 150 mg of CMT was added to 60 mL of dimethylformamide containing 100 mg of H3BTC and magnetically stirred, followed by the addition of 870 mg of Ni(NO3)2·6H2O. The mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and stored at 150 °C for 12 h. The resulting product was soaked in methanol for 48 h to remove the solvent and unreacted ligands. Subsequently, the composite material was centrifuged and washed with water and ethanol. Finally, the product was vacuum dried at 60 °C for 24 h. The final product was decorated as Ni-MOF / CMF-x (x = 50, 100, 150), where x is the amount of CMT. For comparison, pure Ni-MOF was prepared under the same experimental conditions.

[0045] Kapok fibers exhibit a tubular structure with a diameter between 10-40 μm. Figure 1 (a, b) CMT inherits the overall morphology of kapok fiber, with a hollow interior, uniform shape, and smooth surface. Layered tri-shell microtubes were synthesized using a hydrothermal reaction. It can be seen that ultrathin and highly wrinkled Ni-MOF nanosheets are uniformly fixed on the inner and outer surfaces of CMT and intersected with each other, thus obtaining layered tri-shell microtubes with multi-shell heterogeneous interfaces and cavities. Figure 2 The formation of this layered structure can be explained as: Ni 2+ The Ni-MOF crystallizes and grows by being absorbed by CMT via electrostatic attraction, thus creating nucleation centers. Subsequently, the deprotonated H3BTC ligand reacts with Ni... 2+ Coordination and bridging of ordered chains were performed, and the Ni-MOFs self-assembled with the CMT framework into a three-dimensional porous array structure. Furthermore, the effect of CMT dosage on the morphology of Ni-MOF / CMT was investigated. Without CMT, Ni-MOFs underwent free nucleation and growth, forming a layer-by-layer stacked structure composed of aggregated 2D nanosheets. Figure 3 For small amounts of CMT, aggregated nanosheets adhering to the CMT are observed, leading to a reduction in porosity. With increasing CMT content, the material morphology becomes loose and uniform, which may be related to the uniform distribution of nucleation sites. Therefore, the morphology of Ni-MOF / CMT can be precisely controlled by adjusting the amount of CMT. In this strategy, moderate CMT can effectively regulate the aggregation degree of Ni-MOF, resulting in a loose, sheet-like structure. This unique three-dimensional structure can generate void spaces and a larger surface area, which is beneficial for the reflection and scattering of electromagnetic waves.

[0046] Example 2: Preparation of Ni / CMT / PTFE composite material

[0047] Ni-MOF / CMT-150 was placed in a tube furnace and treated at 450 °C under a nitrogen atmosphere for 2 h with a heating rate of 2 °C / min. After cooling to room temperature, Ni / CMT was obtained. Ni / CMT / PTFE composites were prepared by simple mechanical mixing of PTFE and Ni / CMT. In a typical process, Ni / CMT is dispersed in PTFE. Then, after stirring at room temperature for half an hour, an appropriate amount of ethanol was added. The volume ratio of ethanol to PTFE was 1:1. NCPs with Ni / CMT to PTFE mass ratios of 1 wt%, 3 wt%, 5 wt%, and 7 wt% were named NCP-1, NCP-3, NCP-5, and NCP-7, respectively.

[0048] After high-temperature calcination, Ni / CMT retains the morphology of Ni-MOF / CMT, but the size of the nanosheets is shrinking due to the loss of organic ligands at high temperatures. Figure 4 a). Clearly, layered Ni is composed of nanoparticles with a size of approximately 5-20 nm. Figure 4 b). Rapid demulsification can be achieved through mechanical stirring and the addition of ethanol to the Ni / CMT and PTFE mixture. During demulsification, elongated PTFE fibers are formed. Figure 5 These fiber networks wrap around uniformly dispersed Ni / CMT, resulting in a uniformly textured Ni / CMT / PTFE bulk composite material. Figure 6 It can be seen that Ni / CMT is dispersed in PTFE with a highly intact hollow structure. With the increase of Ni / CMT content, the conductive path increases significantly, which is beneficial to the dissipation of electromagnetic waves.

[0049] Application Example 1

[0050] Applications of Ni / CMT / PTFE composite materials in electromagnetic wave absorption:

[0051] To obtain the microwave absorption properties of the Ni / CMT / PTFE composite material, the electromagnetic parameters of the composite material in the 2-18 GHz frequency range were measured using a Ceyear 3672B-S network analyzer. The Ni / CMT / PTFE composite film was cut into rings with an outer diameter of 7.00 mm and an inner diameter of 3.04 mm (thickness of 2.00 mm). Each ring was then placed on a vector mesh analyzer to measure the electromagnetic parameters of the composite material.

[0052] Generally, the ability to absorb electromagnetic waves is determined by electromagnetic parameters. The real part of the dielectric ε′ (real part of the permeability μ′) and the imaginary part of the dielectric ε″ (imaginary part of the permeability μ″) represent the storage and attenuation capabilities of the dielectric (magnetic) energy. Although MOF materials possess outstanding physicochemical properties, unique porous structures, and significant specific surface areas, providing a great advantage in electromagnetic wave absorption, their low dielectric constant limits their ability to effectively absorb microwave energy. The synthesized Ni-MOF has almost unchanged ε′ and ε″ values, at 2.2 and 0.1, respectively. Figure 7 (a, b) This means that most of the incident microwaves penetrated the entire Ni-MOF at the measurement frequency. In contrast, the ε′ and ε″ of the original CMT are 48.7–12.5 and 34.4–16.7, respectively. Figure 7 a, b). This indicates that in this case, the magnetic and dielectric properties are mismatched, reducing the effective absorption of electromagnetic waves. Therefore, introducing Ni-MOF into CMT is an effective strategy to improve MA performance. With the increase of Ni-MOF, the ε′ and ε″ values ​​of Ni-MOF / CMT decrease rapidly with the increase of Ni-MOF quantity. Figure 7 (c, d). As the frequency increases, the ε′ values ​​of Ni-MOF / CMT-50, Ni-MOF / CMT-100, and Ni-MOF / CMT-150 decrease from 6.4 to 4.5, 8.1 to 5.3, and 9.8 to 5.1, respectively. Simultaneously, the ε″ values ​​of Ni-MOF / CMT-50, Ni-MOF / CMT-100, and Ni-MOF / CMT-150 increase from 0.9 to 1.6, from 1.6 to 2.5, and from 2.3 to 2.7, respectively. Therefore, compared to pure CMT and Ni-MOF, the electromagnetic wave absorption capability of Ni-MOF / CMT is significantly improved. Figure 8 As shown, Ni-MOF / CMT-50 exhibits low electromagnetic wave absorption performance, with a minimum RL (RL) min The value is -13.8dB, and the maximum effective absorption bandwidth (EAB) is... max The maximum spectral density (MRD) is 4.6 GHz. With increasing CMT content, Ni-MOF / CMT-100 achieves a wideband MA of 12.2-18 GHz at a thickness of 2.00 mm, and an RLD at 16.9 GHz. min It can reach -21.9dB. In comparison, Ni-MOF / CMT-150 with the best CMT content has a bandwidth of 7.1GHz at 2.4mm and an RL at 2mm. min With a dielectric constant of -59.9 dB, it exhibits the best electromagnetic wave absorption performance in the 10.9-18 GHz range. The excellent dielectric properties of Ni-MOF / CMT indicate that the introduction of CMT can effectively improve the dielectric properties of Ni-MOF while well preserving the structure of Ni-MOF, which is beneficial for electromagnetic wave absorption.

[0053] The electromagnetic wave absorption performance of each sample was analyzed using transmission line theory.

[0054]

[0055] RL=20lg|(Z in -Z0) / (Z in +Z0)| (Equation 2)

[0056] Z in Z0 is the input impedance of the absorber, Z0 is the free space impedance, and μ is the input impedance of the absorber. r relative complex permeability (μ) r =μ′-iμ″), ε r The complex permittivity (ε) r =ε′-iε″), where d is the thickness of the absorber, and c and f are the speed and frequency of light, respectively. To meet practical application requirements, the reflection loss (RL) value of the effective absorbing material should be less than -10dB, which means that the material's absorption rate of electromagnetic waves reaches 90%.

[0057] Figure 9 The electromagnetic parameters of the Ni / CMT / PTFE samples were plotted. Due to poor conductivity at low Ni / CMT contents, NCP-1 exhibited the lowest complex permittivity. With increasing Ni / CMT content, a 3D conductive network emerged, leading to higher conductivity and an increased complex permittivity. The complex permeability values ​​of all Ni / CMT / PTFE samples were almost identical, with no significant attenuation across the entire microwave frequency range. The Ni / CMT / PTFE films also demonstrated highly efficient electromagnetic wave absorption performance in the frequency range of 2-18 GHz. Figure 10 Due to its poor dielectric loss capability, the NCP-0's RL... min It is only -3.45dB, while NCP-1's RL min Increased to -12.95 dB. NCP-3 exhibits low-frequency electromagnetic wave absorption, with an RL value at 5.92 GHz when the thickness is 5.00 mm. min Reaching -59.12, it almost completely covers the C-band. Furthermore, it achieved an EAB of 5.44 GHz with a thickness of 2.4 mm. max Increased Ni / CMT content, NCP-5 at a thickness of 2.1 mm and RL min It can achieve -63.28dB at 11.12GHz. Especially with its ultra-thin coating thickness, NCP-7 achieves an excellent broadband speed of 6.3GHz at 1.8mm, and RL... min-51.93 dB at 1.76 mm. Interestingly, except for NCP-1 with its low Ni / CMT content, all Ni / CMT / PTFE samples exhibited efficient absorption with a medium bandwidth, suggesting they are ideal candidates for lightweight absorbents.

[0058] Application Example 2

[0059] Applications of Ni / CMT / PTFE composite materials in the field of electrothermal heating:

[0060] Figure 11 The Joule thermal properties of Ni / CMT / PTFE films were systematically studied. Figure 11 The image shows the surface temperature of Ni / CMT / PTFE over time under low voltages of 10-30V. At 10V, the film achieves a comfortable temperature of 25°C. The saturation temperature variation with driving voltage is visually represented by infrared thermal imaging. Notably, the surface temperature of Ni / CMT / PTFE can be rapidly switched by adjusting the driving voltage. These results demonstrate that Ni / CMT / PTFE exhibits good Joule heating recyclability, controllability, and stability, making it suitable for thermal management applications. The hydrophobicity of the Ni / CMT / PTFE film, synergistically with its Joule thermal properties, contributes to effective de-icing. Figure 11 As shown in Figure b, blue ice was placed on an inclined Ni / CMT / PTFE heater with a driving voltage of 30V. Within 40 seconds, the ice melted and slid off the film surface, which is important for electromagnetic wave absorption applications in extreme environments.

Claims

1. A method for preparing an electromagnetic wave absorbing composite thin film, characterized in that: Includes the following steps: (1) Carbon microtubes (CMT) were obtained by calcining kapok fibers in a nitrogen atmosphere at a temperature of 750-850℃. (2) CMT, Ni(NO3)2•6H2O and H3BTC were added to dimethylformamide solvent by hydrothermal reaction and the solution was magnetically stirred until it was uniformly mixed. The uniformly mixed solution was transferred to a 100mL hydrothermal reactor and reacted at 150°C for a certain time. After the reaction was completed, it was naturally cooled to room temperature, the precipitate was centrifuged, washed three times with water and three times with ethanol, and dried naturally in the air to obtain gray-black Ni-MOF / CMT powder. The concentration of Ni(NO3)2•6H2O was controlled between 0.014 g / mL and 0.015 g / mL, and the concentration of H3BTC was controlled between 0.0016 g / mL and 0.0017 g / mL; the concentration of CMT added was 0.8 mg / mL to 3 mg / mL. The well-mixed solution is reacted in a sealed reactor for 10-14 hours. (3) Ni-MOF / CMT is calcined in a nitrogen atmosphere at a temperature of 350-500℃ to obtain Ni / CMT; (4) Ni / CMT is dispersed in polytetrafluoroethylene (PTFE), and then a certain amount of ethanol is added and stirred evenly to obtain a flexible Ni / CMT / PTFE composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the nitrogen flow rate is 30-40 mL / min.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the roasting time is 1-2 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the concentration of CMT added is 2.5 mg / mL.

5. The preparation method according to claim 1, characterized in that: In step (3), the nitrogen flow rate is 30-40 mL / min.

6. The preparation method according to claim 1 or 5, characterized in that: In step (3), the roasting time is 1-2 hours.

7. The preparation method according to claim 1, characterized in that: In step (4) above, the mass ratio of Ni / CMT to PTFE is 1%-7%; the volume ratio of ethanol to PTFE is 1-2:

1.

8. The preparation method according to claim 7, characterized in that: In step (4), the mass ratio of Ni / CMT to PTFE is 3%.

9. A Ni / CMT / PTFE composite material prepared by the method for preparing an electromagnetic wave absorbing composite thin film according to any one of claims 1-8.

10. The Ni / CMT / PTFE composite material according to claim 9, characterized in that: In the Ni / CMT / PTFE composite material, the layered hollow structure of Ni / CMT is uniformly encapsulated in PTFE.

11. The application of the Ni / CMT / PTFE composite material as described in claim 9 or 10 in the field of electromagnetic wave absorption and thermally conductive filler.

Citation Information

Patent Citations

  • Electromagnetic wave absorption structure and method for producing the same

    JP2004250643A

  • Electromagnetic wave absorbing film including graphene oxide and manufacturing method thereof

    KR101401542B1